Silk fibroin extraction process and product

CN122940875APending Publication Date: 2026-10-20ZHONGSHAN ZHONGYAN COSMETIC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611444094.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]为了解决现有的丝素蛋白提取工艺的提取效率低,脱胶效果差,提取过程中丝素容易损失,丝素蛋白的得率低、分子量大,易絮凝等技术问题,本发明提供了一种丝素蛋白提取工艺及产物,通过特定的碱液、提取工艺控制,能够快速提取得到分子量小、稳定性好的丝素蛋白;且本发明的提取工艺适用于各种软硬度的蚕丝,应用前景广阔

Benefits of technology

1)本发明采用4-6wt%偏铝酸钠水溶液对蚕丝进行脱胶处理,适配不同软硬蚕丝,脱胶彻底且无丝素损失,能够提取得到分子量≤350Da的小分子丝素蛋白;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of protein extraction technology, and more particularly to a silk fibroin extraction process and product. The steps include: degumming silk to obtain fibroin; dissolving the fibroin in a lithium bromide aqueous solution to obtain a silk fibroin protein solution; and desalting the silk fibroin protein solution to obtain a silk fibroin protein extract. The degumming step includes: placing the silk in an alkaline solution and heating it in a water bath at 85-95°C for 30-60 minutes; the alkaline solution is a 4-6 wt% sodium aluminate aqueous solution; the mass ratio of the fibroin to the lithium bromide aqueous solution is 1:(2-4); and the dissolution conditions are: a dissolution temperature of 90-95°C and a dissolution time of 5-15 minutes. This invention, through specific alkaline solution and extraction process control, can rapidly extract silk fibroin proteins with small molecular weight and good stability; and the extraction process of this invention is applicable to silk of various softness and hardness, with broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of protein extraction technology, and in particular to a silk fibroin extraction process and product. Background Technology

[0002] Silk fibroin is a natural high-molecular-weight protein isolated from natural silk. It possesses excellent biocompatibility, biodegradability, good mechanical properties, and unique bioactivity, showing broad application prospects in various fields such as biomedical materials, tissue engineering scaffolds, cosmetic raw materials, and food additives. The various amino acids, such as glycine and alanine, contained in its molecular structure not only provide a favorable microenvironment for cell growth but also allow for precise adaptation of mechanical properties through molecular conformation regulation. Compared to synthetic polymer materials, it is more easily accepted by the human body or the natural environment, reducing rejection reactions and environmental burden during application. Furthermore, silk fibroin is highly modifiable; its performance can be further optimized through cross-linking, grafting, and other methods, expanding its application scenarios. Therefore, it has become one of the research hotspots in the field of natural polymer materials.

[0003] Current silk fibroin extraction technologies mainly include alkaline degumming, enzymatic degumming, salt solution dissolution, and urea dissolution. Among these, alkaline degumming is widely used due to its simplicity and low cost, while salt solution dissolution has become the mainstream method because it can efficiently disrupt the hydrogen bond network of silk fibroin and achieve rapid dissolution. However, existing extraction technologies still have significant drawbacks, especially the excessively long overall extraction cycle, which restricts their large-scale production and industrial application. For example, traditional alkaline degumming requires holding at a specific temperature for more than 60 minutes, and the subsequent salt solution dissolution process often requires holding at a temperature of 20 minutes or even longer. Combined with the time-consuming washing and filtration processes during desalting and purification, the total extraction time for a single process typically exceeds 3 hours. This excessively long extraction time not only reduces production efficiency but may also lead to molecular weight degradation and impaired bioactivity of silk fibroin due to prolonged high-temperature treatment, affecting the quality and performance of the final product. Therefore, developing a silk fibroin extraction technology that efficiently shortens the extraction time while ensuring product purity and activity has become an urgent technical problem to be solved in this field.

[0004] Chinese invention patent CN111875691B discloses a method for preparing a silk fibroin-sericite composite solution. This method uses a gentle degumming and one-step dissolution process to prepare a high-viscosity, high-molecular-weight silk fibroin-sericite composite solution, solving the problem of large-molecule damage in silk fibroin and improving the mechanical properties of the material to meet the repair needs of hard tissues. However, this technology has a long extraction time, high implementation cost, long dialysis time, and low yield, which cannot meet the needs of industrial production. Chinese invention patent application CN119841923A discloses a silk fibroin material and its extraction method. By introducing an ordered physical stimulation process during silk fibroin extraction, it solves the problem of difficulty in controlling the tertiary structure of silk fibroin in existing technologies, achieving improved physical properties for its application in the pharmaceutical field. Chinese invention patent application CN120829492A discloses a silk fibroin extraction and crystallization strengthening process and its application. By combining calcium chloride-ethanol-water-urea solvent with nanomaterial modification and segmented control of electric field parameters, it solves the performance deficiencies in traditional silk fibroin extraction and crystallization strengthening processes, achieving the performance requirements of high-end applications and optimizing the mechanical and biocompatibility of fiber mats. However, these extraction processes all suffer from technical problems such as long extraction time and low production efficiency.

[0005] Against this backdrop, it is imperative to provide a process that is quick to extract, easy to implement, and capable of producing high-quality silk fibroin. Summary of the Invention

[0006] To address the technical problems of low extraction efficiency, poor degumming effect, easy loss of silk fibroin during extraction, low yield, large molecular weight, and easy flocculation of existing silk fibroin extraction processes, this invention provides a silk fibroin extraction process and product. Through specific alkaline solution and extraction process control, silk fibroin with small molecular weight and good stability can be extracted rapidly. Moreover, the extraction process of this invention is applicable to silk of various softness and hardness, and has broad application prospects.

[0007] The first aspect of this invention provides a silk fibroin extraction process, comprising the following steps: S1. Degumming of silk yields fibroin; S2. Dissolve the silk fibroin in an aqueous lithium bromide solution to obtain a silk fibroin protein solution; S3. The silk fibroin solution is desalted to obtain a silk fibroin extract.

[0008] Optionally, the silk varieties include one or more combinations of Jiangnan silk, Yunnan tussah silk, and castor silk from Yunnan, Guizhou, and Sichuan.

[0009] Further optionally, the alkaline solution is a 4-6 wt% sodium aluminate aqueous solution; examples include 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, and 6 wt%.

[0010] To address the problems of significant damage to silk fibroin and incomplete sericin separation during traditional strong acid and strong alkali degumming processes, this invention optimizes the extraction process by using a 4-6 wt% sodium aluminate aqueous solution as the degumming alkali. The OH- produced by its hydrolysis... - It can gently disrupt the peptide and hydrogen bond network of sericin, while aluminate ions can form reversible complexes with the polar groups in sericin, avoiding the defects of excessive hydrolysis of fibroin by strong acids (such as sulfuric acid) and chain breakage caused by strong corrosion of strong alkalis (such as sodium hydroxide). Sodium aluminate at this concentration has a weak effect on fibroin, acting only on the sericin component. Through this specific mechanism of "selective dissolution-complexation", it can ultimately achieve the effect of completely separating sericin and fibroin in silk without damaging the fibroin.

[0011] Conventional extraction processes using strong acids and alkalis for degumming only yield silk fibroin with a molecular weight exceeding 2000 Da. This invention uses a 4-6 wt% sodium aluminate aqueous solution as the degumming alkali, unexpectedly finding that it not only shortens the extraction time but also significantly reduces the molecular weight of the silk fibroin. It is speculated that traditional strong acids indiscriminately break the peptide bonds of silk fibroin through strong protonation, resulting in a wide molecular weight distribution but an overall large product. Strong alkalis, on the other hand, destroy the higher-order structure of silk fibroin through a highly alkaline environment, but it is difficult to precisely control the degree of peptide chain breakage. Sodium aluminate, however, has a dual specificity: firstly, the weakly alkaline environment generated by its hydrolysis selectively dissolves sericin; secondly, aluminate ions can form weak complexation sites with the carboxyl and hydroxyl groups on the silk fibroin chain. In subsequent dissolution steps, these complexation sites guide lithium bromide to preferentially act on the amorphous peptide bonds of silk fibroin, achieving site-directed mild chain breakage. This avoids the indiscriminate breakage caused by strong acids and alkalis while precisely disintegrating silk fibroin molecules into small fragments. Through the synergistic mechanism of "selective degumming + site-directed chain breaking", the molecular weight of silk fibroin was reduced from more than 2000 Da by conventional methods to a small molecular level of 400 Da. The folding of chemical bonds (such as β bonds) in silk fibroin molecules was avoided at the molecular level, which inhibited aggregation and further improved the stability of the extracted product.

[0012] Most preferably, the degumming process includes: placing the silk in a 5 wt% sodium aluminate aqueous solution and heating it in a 90°C water bath for 50 minutes.

[0013] Optionally, the degumming process includes: placing the silk in an alkaline solution and heating it in a water bath at 85-95°C for 30-60 minutes.

[0014] To address the problems of time-consuming and inefficient existing degumming processes, this invention further optimizes the degumming process by placing the silk in a sodium aluminate alkaline solution and heating it in a water bath at 85-95°C for 30-60 minutes for degumming. On one hand, the 85-95°C water bath temperature can increase the molecular motion rate of the sodium aluminate aqueous solution, enhancing the degumming effect of OH-. - This temperature range not only improves the efficiency of aluminate ions penetrating into the sericin layer, but also avoids the problems of slow reaction rate between alkali and sericin and incomplete degumming at low temperatures (<80℃), and the risk of damage to silk fibroin due to the sudden increase in the corrosiveness of alkali at ultra-high temperatures (>100℃). By controlling the specific degumming temperature and time, the efficient removal of sericin by alkali is achieved, and the technical effect of shortening the time consumed in the degumming stage and compressing the overall extraction time for subsequent steps is realized.

[0015] Optionally, the ratio of the silk and the sodium aluminate aqueous solution is 8-12g:100mL; examples include 8g:100mL, 9g:100mL, 10g:100mL, 11g:100mL, and 12g:100mL.

[0016] Optionally, the fibroin is 75-85 wt% of the silk mass; more preferably, the fibroin is 78-80 wt% of the silk mass. Since silk is mainly composed of fibroin and sericin, when fibroin accounts for 80% of the silk mass, the mass ratio of fibroin to sericin can be approximately considered to be 8:2. The extraction objective of this invention is to minimize fibroin loss, thus requiring the fibroin to be 78-80 wt% of the silk mass. A lower percentage of fibroin means greater fibroin loss during extraction, resulting in a correspondingly lower yield of fibroin protein.

[0017] Optionally, the mass ratio of the silk fibroin to the lithium bromide aqueous solution is 1:(2-4); examples include 1:2, 1:3, and 1:4.

[0018] Improving the solubility of silk fibroin often results in the loss of silk fibroin protein, making it difficult to balance the extraction efficiency and yield of silk fibroin protein. This invention preferably uses a mass ratio of silk fibroin to lithium bromide aqueous solution of 1:(2-4), combined with a specific degumming treatment to overcome this problem. Lithium bromide, as a strongly polar solvent, forms coordination bonds with the amide groups of silk fibroin through lithium ions, thereby destroying the crystalline structure of silk fibroin. When the mass ratio is less than 1:2, the amount of lithium bromide is insufficient and cannot fully destroy the crystalline region of silk fibroin, resulting in incomplete dissolution. When the mass ratio is greater than 1:4, excessive lithium bromide will over-solventize silk fibroin molecules, causing some silk fibroin peptide chains to be lost with the solvent. The 1:(2-4) ratio allows lithium bromide to achieve just the right amount of solubilization of silk fibroin, achieving the technical effect of accelerating dissolution while avoiding the loss of silk fibroin during extraction.

[0019] Optionally, the mass concentration of the lithium bromide aqueous solution is 40-60%; examples include 40%, 45%, 50%, 55%, and 60%; and more preferably 50%.

[0020] Optionally, the conditions for the dissolution treatment are: dissolution temperature 90-95℃, dissolution time 5-15min.

[0021] To address the issues of easy flocculation, poor stability, and difficulty in obtaining small molecule products from silk fibroin solutions, this invention employs a dissolution process at 90-95℃ for 5-15 minutes. Within this temperature range, the solvation capability of lithium bromide is in a "mild disintegration" range: below 90℃, lithium bromide is insufficient to disrupt the crystalline region of silk fibroin, resulting in high molecular aggregation and easy flocculation due to intermolecular forces; above 95℃, excessive thermal motion can lead to disordered breakage of silk fibroin peptide chains, generating too many fragments that affect subsequent applications; while the 5-15 minute time allows lithium bromide to gradually disintegrate the multi-level structure of silk fibroin (from the crystalline region to the amorphous region) while maintaining the basic integrity of the peptide chains; through the control of specific dissolution conditions, rapid dissolution of silk fibroin can be achieved, ultimately improving the stability of silk fibroin and obtaining small molecule silk fibroin.

[0022] Furthermore, in order to balance dissolution speed and implementation cost, the mass ratio of silk fibroin to lithium bromide aqueous solution can optionally be 1:(2-3), and the dissolution time can be 10-15 min.

[0023] Optionally, the desalting step includes: using a spiral wound ultrafiltration membrane to retain the silk fibroin solution, washing the retained product with water until the conductivity is 200-500 μS / cm (to maintain the protein in isoelectric equilibrium in the aqueous solution), and obtaining silk fibroin.

[0024] Optionally, the spiral-wound ultrafiltration membrane has a molecular weight cutoff of ≥5KD. During the investigation, it was found that if the membrane pore size is not properly selected, not only will the desalination effect be poor, but protein molecules will also aggregate, fold, and denature on the membrane surface, ultimately forming solid precipitates that lose their activity and reuse value.

[0025] A second aspect of the present invention provides a silk fibroin obtained by the extraction process described above, wherein the molecular weight of the silk fibroin is ≤400 Da.

[0026] Beneficial effects: This invention provides a silk fibroin extraction process and product, which has the following advantages: 1) This invention uses a 4-6wt% sodium aluminate aqueous solution to degumme silk, which is suitable for silk of different softness and hardness. The degumming is thorough and there is no loss of silk fibroin. Small molecule silk fibroin with a molecular weight ≤350Da can be extracted. 2) This invention uses a 1:(2-4) ratio of silk fibroin to lithium bromide aqueous solution, which reduces the amount of solvent used, lowers the cost, and shortens the dissolution time. 3) The present invention uses a degumming treatment condition of 85-95℃ water bath heating for 30-60 minutes and sets the dissolution temperature to 90-95℃. During the extraction process, the silk fibroin only needs 5-15 minutes to completely dissolve, and the obtained silk fibroin has no flocculation and excellent room temperature stability. 4) This invention uses a spiral wound ultrafiltration membrane with a molecular weight cutoff of ≥5KD to desalinate the silk fibroin solution, which can completely separate lithium bromide and improve the yield of silk fibroin. 5) The extraction process of this invention is simple to operate and has high extraction efficiency, which can meet the requirements of industrial mass production; 6) The extraction method of this invention is applicable to multiple varieties of silk (such as Jiangnan silk, Yunnan tussah silk, and castor silk from Yunnan, Guizhou and Sichuan), and the extracted products have good stability and a wide range of applications; 7) Verified by cell anti-photoaging efficacy test and cell anti-wrinkle and firming efficacy test, the silk fibroin solution extracted by this invention has significant anti-photoaging, anti-wrinkle and firming effects at the cellular level. Attached Figure Description

[0027] Figure 1 Photograph of the silk fibroin obtained in step S1 of Example 1; Figure 2 Photograph of the silk fibroin solution obtained in step S2 of Example 1; Figure 3 Photograph of the silk fibroin extract obtained in step S3 of Example 1; Figure 4 Results of the cell anti-photoaging efficacy test of the silk fibroin extract obtained in Example 1; Figure 5 The results of the cell anti-wrinkle and firming efficacy test of the silk fibroin extract obtained in Example 1. Detailed Implementation

[0028] The silk used in the following examples comes from the following sources.

[0029] Jiangnan Silk: Sourced from Zhejiang Zhongwei Silk Group Co., Ltd.; this variety of silk has a moderate hardness.

[0030] Yunnan tussah silk: sourced from Zhejiang Zhongwei Silk Group Co., Ltd.; this variety of silk has a relatively hard texture, with coarser fibers, a yellowish-brown or grayish-brown color, low sericin content, a stiff texture, high loft, and strong corrosion resistance.

[0031] Castor silk from Yunnan, Guizhou, and Sichuan: sourced from Zhejiang Zhongwei Silk Group Co., Ltd.; this variety of silk has a softer texture and is finer and softer.

[0032] Unless otherwise specified, all raw materials, equipment and other consumables used in this invention are commercially available.

[0033] Example 1 This embodiment provides a silk fibroin extraction process and product, the steps of which include: S1. Degumming treatment: 10g of silk (Jiangnan silk variety) was placed in 100mL of alkaline solution (5wt% sodium aluminate aqueous solution) and heated in a 90℃ water bath for 50min; the solid was collected, washed with water, and dried at 90℃ to obtain fibroin ( Figure 1 ); S2. Dissolution treatment: The silk fibroin was dissolved in a 50wt% lithium bromide aqueous solution (the mass ratio of silk fibroin to lithium bromide aqueous solution was 1:3) and dissolved in a 90℃ constant temperature water bath for 10 min to obtain a silk fibroin protein solution. Figure 2 ); S3. Desalination treatment: The silk fibroin solution was treated with a spiral-wound ultrafiltration membrane with a molecular weight cutoff of ≥5KD (from Hangzhou Ruina Membrane Engineering Co., Ltd.). The retained product was washed with water until the conductivity was 200-500μS / cm to obtain the silk fibroin extract. Figure 3 ).

[0034] The fibroin obtained after drying in step S1 weighed 7.85g (with a mass loss rate of 21.5wt%), meaning that 2.15g of sericin in the silk was dissolved after water bath heating.

[0035] Following the method in Example 1, 50g of silk was extracted. After drying in step S1, 39.3g of silk fibroin product was obtained. See the image below. Figure 1 .

[0036] Example 2 This embodiment provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Embodiment 1; the difference is that the silk variety is Yunnan tussah silk.

[0037] Example 3 This embodiment provides a silk fibroin extraction process and product, and the specific implementation method is the same as in Embodiment 1; the difference is that the silk variety is castor silk from Yunnan, Guizhou and Sichuan.

[0038] Example 4 This embodiment provides a silk fibroin extraction process and product, and the specific implementation method is the same as in Embodiment 1; the difference is that the mass ratio of silk fibroin and lithium bromide aqueous solution is 1:4.

[0039] Comparative Example 1 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference being that the alkaline solution is a 5wt% calcium chloride aqueous solution.

[0040] Comparative Example 2 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference being that the alkaline solution is a 5wt% aluminum hydroxide aqueous solution.

[0041] Comparative Example 3 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the alkaline solution is replaced with a 5wt% nitric acid aqueous solution.

[0042] Comparative Example 4 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the alkaline solution is replaced with a 5wt% aqueous carbonate solution.

[0043] Comparative Example 5 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference being that the alkali solution is a 7wt% sodium aluminate aqueous solution.

[0044] Comparative Example 6 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference being that the alkali solution is a 10wt% sodium aluminate aqueous solution.

[0045] Comparative Example 7 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference being that the alkali solution is a 2wt% sodium aluminate aqueous solution.

[0046] Comparative Example 8 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the water bath heating temperature in step S1 is 70°C.

[0047] Comparative Example 9 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the water bath heating temperature in step S1 is 80°C.

[0048] Comparative Example 10 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the water bath heating temperature in step S1 is 100℃.

[0049] Comparative Example 11 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the water bath heating temperature in step S1 is 110°C.

[0050] Comparative Example 12 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that the water bath dissolution temperature in step S2 is 80°C.

[0051] Comparative Example 13 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that step S1 is as follows: 10g of silk (Yunnan tussah silk) is placed in 100mL of alkaline solution (5wt% aluminum hydroxide aqueous solution) and heated in a water bath at 90℃ for 70min; the solid is collected, washed with water, and dried.

[0052] The yield of silk fibroin after desalting in this comparative study was too low, only 6.45g; the residual sericin content was as high as 35.5%.

[0053] Comparative Example 14 This comparative example provides a silk fibroin extraction process and product, with the specific implementation method being the same as in Example 1; the difference is that step S1 is as follows: 10g of silk (the variety is castor silk from Yunnan, Guizhou and Sichuan) is placed in 100mL of alkaline solution (5wt% aluminum hydroxide aqueous solution) and heated in a water bath at 90℃ for 30min; the solid is collected by centrifugation, washed with water, and dried.

[0054] Performance testing 1. Dissolving time In Examples 1-4 and Comparative Examples 1-14, step S2 involved dissolving the silk fibroin in a water bath until it was completely dissolved. The dissolution time for each example is recorded in Table 1.

[0055] 2. Degumming and desalination effects The silk fibroin extracts obtained in S1 and S3 of Examples 1-4 and Comparative Examples 1-14 were weighed (referred to as m1 and m2 respectively), and the weighing results are recorded in Table 1.

[0056] For Jiangnan silk: The theoretical weight of fibroin after degumming is 8g. If m is greater than 8g, it indicates incomplete degumming; if m is less than 8g, it indicates complete degumming. The closer m is to 8g, the less fibroin protein loss there is. For tussah silk and castor silk, the theoretical weight of fibroin after degumming is 7g.

[0057] 3. Molecular weight of silk fibroin Referring to YY / T 1950-2024 "Tissue Engineering Medical Devices - Silk Fibroin", the weight-average molecular weight Mn of the silk fibroin extracts obtained in Examples 1-4 and Comparative Examples 1-14 was tested, and the results are recorded in Table 1.

[0058] 4. Room temperature stability of silk fibroin The silk fibroin solutions extracted in Examples 1-4 and Comparative Examples 1-14 were observed after being left at room temperature for 24 hours. The results are recorded in Table 1. Stable indicates no flocculation, while unstable indicates flocculation.

[0059] Table 1

[0060] In Table 1, “ / ” indicates that the measurement was not performed.

[0061] The data in Table 1 shows that the specific alkaline solution (sodium aluminate aqueous solution), specific degumming process, and dissolution process of the present invention work together to quickly extract fibroin from silk in just 5-15 minutes. Moreover, the fibroin has a small molecular weight, does not have flocculation problems, and has excellent stability at room temperature.

[0062] Comparing Example 1 and Comparative Examples 1-4, it can be seen that the present invention has tried a variety of degumming reagents. However, the use of calcium chloride, aluminum hydroxide, nitric acid, or carbonic acid to treat silk results in excessive degumming, high fibroin loss, low fibroin protein yield, and excessively high and unstable molecular weight of the obtained fibroin protein, which is prone to flocculation. It is speculated that the high molecular weight leads to a greater tendency for β-bond folding and aggregation in the fibroin protein molecule, thus causing flocculation problems. Comparing Example 1 and Comparative Examples 5-7, it can be seen that when using sodium aluminate aqueous solution to degumme silk, the concentration of sodium aluminate aqueous solution needs to be controlled within a specific range in order to improve the treatment efficiency while avoiding fibroin loss. When the concentration of sodium aluminate aqueous solution is too high or too low, it is impossible to balance the treatment efficiency and fibroin protein yield, and ensure sufficient degumming.

[0063] Comparing Example 1 and Comparative Examples 8-13, it can be seen that the temperature settings for degumming and dissolving processes have a crucial impact on the extracted product. When the degumming temperature is too low, it takes 2-3 hours to dissolve the silk fibroin; a low dissolving temperature also leads to an excessively long dissolving time; while when the degumming temperature is too high, it causes the sericin and silk fibroin to mix, neither of which meets the requirements for use.

[0064] Comparative Examples 1-3 and Comparative Examples 13 and 14 show that the extraction process of the present invention is applicable to silkworm silk of different hardness, and can achieve good extraction results for silkworm silk from Jiangnan, tussah silk from Yunnan, and castor silk from Yunnan, Guizhou, and Sichuan. Compared with conventional methods, it significantly shortens the extraction time of silk fibroin, avoids the loss of silk fibroin during the extraction process, improves the yield and stability of silk fibroin, and has excellent extraction effect.

[0065] 5. Silk fibroin efficacy test The silk fibroin solution extracted in Example 1 was used for cell anti-photoaging efficacy testing and cell anti-wrinkle and firming efficacy testing. The test methods are described below, and the test results are shown in the figure. Figure 4 , Figure 5 .

[0066] (1) Cell collection and grouping for plating: Human fibroblasts were harvested when their confluence reached approximately 85% under a microscope. The original culture medium was discarded in a clean bench, and the cells were rinsed once with PBS. 1 mL of 0.25% trypsin (containing 0.02% EDTA) was added to wet the bottom of the plate, and the plate was incubated at 37°C for approximately 3 minutes for digestion. After most cells were observed to have detached under a microscope, 2 mL of complete culture medium was added to stop the digestion. The plate was centrifuged at 1000 rpm for 5 minutes. The supernatant was discarded, and the cells were resuspended in 1 mL of complete culture medium and counted using an automated cell counter. 6000 cells / 100 μL were added to each well of a 24-well plate and incubated at 37°C with 5% CO2 for 24 hours.

[0067] (2) Adding medicine The following day, cell adhesion was observed under a microscope. 100 μL of complete serum medium (blank control wells) or 100 μL of DMEM medium containing the test sample (test wells) was added, with three replicates for each concentration. 100 μL of complete medium or PBS buffer was added to the edge wells. The plate was then incubated at 37°C with 5% CO2 for 24 hours.

[0068] The information on the tested samples is shown in Table 2.

[0069] Table 2

[0070] (3) Ultraviolet irradiation 24 hours later, the model group, sample group, and positive group samples were placed under a UV irradiator and exposed to 2000 mJ / cm². 2 Treat under ultraviolet light for 5 minutes. After irradiation, incubate at 37°C in a 5% carbon dioxide incubator for 24 hours.

[0071] (4) Collect cell supernatant After 24 hours, 180 μL of culture supernatant was collected from each well into a 0.2 mL sterile eight-tube strip for immediate testing or freezing at -80°C.

[0072] (5) ELISA detection The anti-photoaging efficacy was tested according to the instructions for use of the MMP-1 enzyme-linked immunosorbent assay kit.

[0073] The anti-wrinkle and firming efficacy of the Type I collagen protein-linked immunosorbent assay kit was tested according to the instructions for use.

[0074] (6) Results Analysis GraphPad Prism was used for plotting, and the results are expressed as Mean ± SD; t-test statistical analysis was used for comparisons between groups; all statistical analyses were two-tailed.

[0075] Figure 4 The results of the anti-photoaging efficacy test showed that, with the relative expression level of MMP-1 in the blank control group as 100%, the MMP-1 expression levels in the 2.25%, 1.125%, and 0.5625% silk fibroin solution sample groups (i.e., the silk fibroin solution of Example 1) were 68.26%, 56.44%, and 34.09% lower than those in the model group, respectively. The results showed significant differences, indicating that the silk fibroin solution extracted in this invention has anti-photoaging efficacy at the cellular level.

[0076] Figure 5 The results of the cell anti-wrinkle and firming efficacy test showed that, with the relative expression level of type I collagen (Col-I) in the blank control group as 100%, the expression level of type I collagen in the 1.125% and 0.5625% silk fibroin solution sample groups increased by 35.55% and 25.73% respectively compared with the model group, and the results showed significant differences, indicating that the silk fibroin solution extracted in this invention has anti-wrinkle and firming effects at the cellular level.

Claims

1. A silk fibroin extraction process, characterized in that the steps include... include: S1. Degumming of silk yields fibroin; S2. Dissolve the silk fibroin in an aqueous lithium bromide solution to obtain a silk fibroin protein solution; S3. Desalting the silk fibroin solution to obtain a silk fibroin extract; The degumming process includes: placing the silk in an alkaline solution and heating it in a water bath at 85-95°C for 30-60 minutes; The alkaline solution is a 4-6 wt% sodium aluminate aqueous solution; The mass ratio of silk fibroin to lithium bromide aqueous solution is 1:(2-4); The conditions for the dissolution treatment are: dissolution temperature 90-95℃, dissolution time 5-15min; The desalination process includes: using a spiral-wound ultrafiltration membrane to retain the silk fibroin solution, washing the retained product with water until the conductivity is 200-500 μS / cm, and obtaining a silk fibroin extract.

2. The silk fibroin extraction process according to claim 1, characterized in that, The degumming process includes: placing the silk in a 5wt% sodium aluminate aqueous solution and heating it in a 90°C water bath for 50 minutes.

3. The silk fibroin extraction process according to claim 1, characterized in that, The spiral wound ultrafiltration membrane has a molecular weight cutoff of ≥5KD.

4. The silk fibroin extraction process according to claim 1, characterized in that, The mass concentration of the lithium bromide aqueous solution is 40-60%.

5. The silk fibroin extraction process according to claim 4, characterized in that, The mass concentration of the lithium bromide aqueous solution is 50%.

6. The silk fibroin extraction process according to claim 1, characterized in that, The ratio of silk and sodium aluminate aqueous solution is 8-12g:100mL.

7. The silk fibroin extraction process according to claim 6, characterized in that, The ratio of silk and sodium aluminate aqueous solution is 10g:100mL.

8. The silk fibroin extraction process according to claim 1, characterized in that, The fibroin is 75-85 wt% of the weight of silk.

9. The silk fibroin extraction process according to claim 1, characterized in that, The silk varieties include one or more combinations of Jiangnan silk, Yunnan tussah silk, and castor silk from Yunnan, Guizhou, and Sichuan.

10. A silk fibroin extracted by the extraction process according to any one of claims 1-9, characterized in that, The molecular weight of the silk fibroin is ≤400 Da.

Citation Information

Patent Citations

  • A method for preparing a silk fibroin-sericin composite solution

    CN111875691B

  • Silk fibroin material and extraction method thereof

    CN119841923A

  • Silk fibroin extraction and crystallization strengthening process and application thereof

    CN120829492A